Multi-hop ESP-Mesh Network and MQTT Protocol for Smart Light Systems in High-Rise Buildings - Januarman Maulana Putra; Misbahuddin Misbahuddin; Sudi Mariyanto Al Sasongko (Universitas Ahmad Dahlan, 2022)
When a high-rise building's lights are not required because they are frequently left on, electrical energy is wasted as a result of this.Â The smart light is one of the effective ways to energy saving in a building. This study aims to create a smart light system using the ESP-Mesh network and the MQTT protocol to control the turn on/off of all lights in all rooms of a high-rise building. The ESP-Mesh network is a mesh of ESP8266 devices that are designed for multi-hop transmission. The MQTT is one of the widely used IoT protocols that allows a smartphone to control the lights in every room in a mesh topology via the internet remotely. The performance evaluation shows that a multi-hop ESP-Mesh is better than that a Single-hop ESP8266 in signal strength. The signal strength of the ESP8266 single-hop is bad. Meanwhile, the signal strength of the multi-hop ESP-Mesh is good in all rooms. Furthermore, The functional tests of the multi-hop ESP-Mesh show that although there are various broken paths caused by several disconnected nodes, all lights can be turned on or off suitably through the command from the smartphone switch. Turning off the not-required lights by smart light systems can help save energy.